MORPHOMETRIC DIFFERENCES BETWEEN HONEY BEES (Apis mellifera carpatica) POPULATIONS FROM TRANSYLVANIAN AREA - L. AL. MĂRGHITAŞ; ORSOLYA PANITI-TELEKY; D. DEZMIREAN; RODICA MĂRGĂOAN; CRISTINA BOJAN; C. COROIAN; LAURA LASLO; ADELA MOISE (Scientific Papers Animal Science and Biotechnologies, 2023)
The result of the long evolutionary process formed, by natural selection, variable races and ecotypes which are biological and ecological differentiated. The Romanian, Apis mellifera carpatica is the most adapted and the most efficient species at the local conditions. Morphometric measurements were the major criteria for classification described by Ruttner (1988) and are the basis of our study. In this way 8 morphometric characters of honeybees from Transylvanian region were measured. The data obtained show that the honeybees’ ecotype genes are mixed due to the migratory beekeeping.